Analysis of time-switching and power-splitting protocols in wireless-powered cooperative communication system - Ponnimbaduge Perera T. D. Tarindu Dilshan (2018, 2018)
SWIPT techniques combined with wireless cooperative communication provides a sustainable solution to extend the lifetime of the communication networks. It prolongs the battery life of wireless low-powered devices and enables additional efficiency in terms of power in wireless communications. This paper explores performance difference of two simultaneous wireless information and power transfer (SWIPT) protocols named Time-Switching (TS) and Power-Splitting (PS). Two identical decode-and-forward relaying communication networks with multiple relays are considered, where energy constrained relay nodes harvest energy from the received Radio Frequency (RF) and use harvested energy to assist information transmission between the source and the destination. All relay nodes in one network use TS protocol while the relay nodes in the other network use PS protocol. In particular, we evaluate throughput and outage probability of maximal ratio combiner (MRC) output at the destination node of both systems. In order to evaluate throughput, outage probability is derived for delay-limited transmission mode. The numerical results provide practical insight into the performance difference in various system parameters for both TS and PS protocols. Simulation results obtained depict that the TS protocol is superior to PS protocol in performance parameters, BER, Outage probability and throughput in low transmission rate. However, in higher transmission rates PS becomes superior to TS protocol, though overall performance reduce compare to lower transmission rate.